Relationship Between Nutritional Status and Quality of Life of Advanced Cancer Patients in Selected Hospices in Peninsular Malaysia - Shahmoradi, Negar (2010)
n Malaysia, cancer is ranked third among most frequent causes of medically certified deaths. A total of 75,744 new cancers cases were diagnosed among Malaysians in the years 2003-2005. Cancer and cancer therapy associated complications tend to change patient’s metabolism and nutritional status and in general quality of life (QOL). In the advanced stages when the disease becomes incurable, and treatment has failed, patients often seek the assistance of hospice facilities for palliative care. The objective of this cross-sectional study was to determine the relationship between nutritional status and quality of life among advanced cancer patients in hospice home care, as well as to determine the significant predictors of nutritional status. The study also examined the relationship between subjective indicators and objective indicators of nutritional status. The study was conducted on 61 patients cared by selected hospices in Peninsular Malaysia. To be eligible for this study, patients were screened for functional status using the Eastern Cooperative Oncology Group (ECOG) scale. Patients with ECOG 0-3 indicating good to fair functional status were recruited with informed consent. Information on socio-demographic, disease status, nutritional status and quality of life, complementary and alternative medicine use, nutritional support, were obtained. Assessment of nutritional status was performed using the Patient-Generated Subjective Global Assessment (PG-SGA), dietary intake and anthropometry measurements. Anthropometry evaluations included height, weight, triceps skinfold, mid-upper arm circumference and arm muscle area. The Hospice Quality of Life Index (HQLI) was used to determine quality of life of the subjects. Patients were between 18 to 74 years old and the mean age was 59.2 ± 12.5 years. Males comprised 45.9% of the sample while 54.1% of them were females. Chinese subjects (67.2%) were predominant, followed by Malays (18%) and Indians (14.8%). The primary disease stage for majority of patients (72.1%) was stage four. The most common cancers were breast (18%), rectum (13.1%) and colon (13.1%). The PG-SGA found 14.7% (9) of 61 patients to be well nourished, 52.5% (32) were moderately or suspected of being malnourished and 32.8% (20) of them were severely malnourished. The mean total PG-SGA score was 13.6 ± 7.0, which indicated a critical need for nutrition intervention. In addition, the negative correlation was found between PG-SGA score and objective indicators of nutritional status. General Linear Model (GLM) univariate analysis revealed that only ethnicity (p=0.016), ECOG status (p=0.000), cancer duration (p=0.022) and energy intake (p=0.000) were significantly related to nutritional status. These four variables were able to explain 63.8% of the total variation in nutritional status. In terms of quality of life, the total HQLI mean score for all subjects was 189.9 ± 51.7. Functional well-being subscale scores were the lowest among the three subscales, followed by psychophysiological and social/ spiritual well-being subscale scores. GLM showed that PG-SGA score (p=0.000) and ECOG (p=0.016) were found to be significant predictors of total quality of life score. These two variables explained 43.9% of the total variation in total quality of life score. PG-SGA score showed a larger effect size (>0.15)on quality of life indicating a stronger effect than functional ability as determined by ECOG. In addition, PG-SGA score and ECOG were the significant predictors for psychophysiological and functional domains of quality of life. No significant predictors were found for social/spiritual domain. In conclusion, these findings showed a high prevalence of malnutrition among advanced cancer patients in hospice care. The results also revealed that patients with poorer nutritional status had lower quality of life. The negative correlation between PG-SGA score and objective indicators of nutritional status showed that PG-SGA score can be applied instead of several objective measurements for assessing nutritional status. Therefore, this study has contributed to the new knowledge base on the relationship between nutritional status and quality of life of cancer patients in hospice care that has not been previously reported in Malaysia.